Role of Consumer Motivation Factors in Online Newspaper Consumption: A Conceptual Framework - Pahore, Muhammad Ramzan; Abdul Hamid, Norsiah; Ismail, Awan (2018)
The role of consumer motivation factors in online newspaper consumption cannot be ignored. Since the emergence of online newspapers two decades ago, the academia have not really delved into the factors that contribute to improved access and use of online newspapers in developing countries. Hence, this study proposes a conceptual framework which highlights the influence of consumer motivation factors on online newspaper consumption in the current ambiance of digital technology. Furthermore, the study aims to propose factors that contribute to increasing online newspaper consumption. This study will contribute to the body of knowledge as well as the practical field in guiding policy makers and media organizations as to the type of content people are willing to consume. This will help to retain extant consumers and attract new consumers on the basis of content provided to the audience